2020
DOI: 10.18502/jfrh.v14i1.3783
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Dydrogesterone and GnRH Antagonists for Prevention of Premature LH Surge in IVF/ICSI Cycles: A Randomized Controlled Trial

Abstract: Objective: To compare the effect of dydrogesterone and GnRH antagonists on prevention of premature luteinizing hormone (LH) surge and pregnancy outcomes in infertile women undergoing IVF/ICSI. Materials and methods: In a Randomized controlled trial (RCT), two-hundred eligible women undergoing in vitro fertilization (IVF) /intracytoplasmic sperm injection (ICSI) treatment were randomly assigned into two groups. Human menopausal gonadotropin (HMG) was administered for controlled ovarian stimulation (COS) i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 26 publications
0
7
0
Order By: Relevance
“…The study that best aligns with our reported CLBRs demonstrated that women aged between 35 and 40 years achieved a CLBR of approximately 51–66% in double-ET and 56–70% in single-ET, without specifying the stimulation protocol ( Mejia et al , 2021 ). PPOS-related protocols are preferable for older women or those with low ovarian reserve because they are better at preventing early LH surges than GnRH antagonists and thus help in obtaining more mature oocytes ( Hossein Rashidi et al , 2020 ). Perhaps for this reason, the PPOS-related scheme has an advantage over the traditional scheme in women above 40 years old.…”
Section: Discussionmentioning
confidence: 99%
“…The study that best aligns with our reported CLBRs demonstrated that women aged between 35 and 40 years achieved a CLBR of approximately 51–66% in double-ET and 56–70% in single-ET, without specifying the stimulation protocol ( Mejia et al , 2021 ). PPOS-related protocols are preferable for older women or those with low ovarian reserve because they are better at preventing early LH surges than GnRH antagonists and thus help in obtaining more mature oocytes ( Hossein Rashidi et al , 2020 ). Perhaps for this reason, the PPOS-related scheme has an advantage over the traditional scheme in women above 40 years old.…”
Section: Discussionmentioning
confidence: 99%
“…According to the findings, to inhibit a premature increase in LH in IVF cases, Duphaston is used as a suitable alternative to Cetrotide in patients undergoing ovarian stimulation because it is more effective and has fewer side effects than Cetrotide. Moreover, Duphaston may be a better alternative in clinical practice because oral administration is more patient-friendly than parenteral administration [22] . The limitations of this study were its non-pregnancy and neonatal outcomes.…”
Section: Discussionmentioning
confidence: 99%
“…Dydrogesterone, as a powerful player in LPD management, can synergize with other medications to create a more effective and holistic treatment approach. This might involve the integration of dydrogesterone with other interventions commonly employed in fertility treatments, such as gonadotropins and gonadotropin-releasing hormone (GnRH) agonists [ 61 ].…”
Section: Reviewmentioning
confidence: 99%